2014
DOI: 10.1155/2014/949128
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Field-Wind Velocity Field Optimum Control of Greenhouse Environment Based on CFD Model

Abstract: The computational fluid dynamics technology is applied as the environmental control model, which can include the greenhouse space. Basic environmental factors are set to be the control objects, the field information is achieved via the division of layers by height, and numerical characteristics of each layer are used to describe the field information. Under the natural ventilation condition, real-time requirements, energy consumption, and distribution difference are selected as index functions. The optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Simplified method 62 [19,32,[37][38][39]46,49,76,78,83,91,95,99,100,106,[108][109][110][111][113][114][115][116][120][121][122][123]126,129,131,133,136,[141][142][143][144][145][146][147][148][149]151,[153][154][155][156][159][160][161][163][164]…”
Section: Radiation Model Number Of Documents Referenceunclassified
See 1 more Smart Citation
“…Simplified method 62 [19,32,[37][38][39]46,49,76,78,83,91,95,99,100,106,[108][109][110][111][113][114][115][116][120][121][122][123]126,129,131,133,136,[141][142][143][144][145][146][147][148][149]151,[153][154][155][156][159][160][161][163][164]…”
Section: Radiation Model Number Of Documents Referenceunclassified
“…Regarding the contribution in number of works developed with the presence of crops, it is worth mentioning Mexico, where 10 publications with this approach originated. These works allowed researchers to determine that when the location of the crop is parallel to the air flow, the conditions of humidity and CO 2 concentration improve and not the thermal gradient, although the authors emphasized that the conditions generated are optimal for the growth and development of the tomato crop [153]. These studies also identified that the effect on the air flow velocity generated by the different types of crops depends on the morphology and porosity degree of the plant [109].…”
Section: Presence Of Crop Number Of Publicationsmentioning
confidence: 99%
“…With the characteristics of less cost and time consuming, computational fluid dynamics (CFD) is commonly employed to simulate indoor thermal environment [22]. rough years of development, CFD simulation can predict indoor velocity distribution, indoor temperature distribution, and indoor air quality accurately [23][24][25].…”
Section: Cfd Simulationmentioning
confidence: 99%
“…We set the least squares cell-based for the gradient and standard for the pressure. The momentum, energy, and H 2 O were set to the second order upwind, turbulent dissipation rate, turbulent kinetic energy, and the DOs were set to first order upwind [31]. The underrelaxation factors of pressure, momentum, turbulent dissipation rate, and turbulent kinetic energy were set to 0.3, 0.7, 0.8, and 0.8, respectively, and the others were set to 1.…”
Section: Analytical Setting and Meshingmentioning
confidence: 99%